PENGARUH PEMBAKARAN BERULANG PADA LAHAN GAMBUT TERHADAP BEBERAPA KARAKTERISTIK TANAH DI DESA RASAU JAYA UMUM KABUPATEN KUBU RAYA KALIMANTAN BARAT - Astuti, Yuliana; Astiani, Dwi; Herawatiningsih, Ratna (JURNAL HUTAN LESTARI, 2020)
The National Disaster Management Agency (BNPB) identifies eight provinces considered prone to forest and land fires in Indonesia. Four provinces are in Sumatra and four are in Kalimantan, one of which is West Kalimantan. Forest and land fires seem to have become a disaster in West Kalimantan, especially every dry season. Burning activies in the preparation of land for agriculture in the village of Rasau Jaya General is still using a relatively simple technology, namely the method of "slash and burn". The impacts caused by the peat fire process are in the form of water vapor from the combustion process in the air so that smoke formed which is very thick, causes environmental pollution and can affect soil conditions such as physical and chemical properties of peat soils. The purpose of this study was to obtain information about the effects of repeated burning on peatlands on soil characteristics in Rasau Jaya Umum Village, Kubu Raya Regency, West Kalimantan. This research was conducted by survey method and carried out with purposive sampling on 3 research sites, which were on land that had repeated burning twice, 4 times and 5 times. Soil physical properties observed were peat maturity (fiber content), water content, soil moisture, water level and bulk density. The level of fertility of peatlands is influenced by the chemical nature of the soil. The chemical nature of the soil is one of the limiting factors for knowing nutrients in the soil that are beneficial for plant growth. Determination of the level of soil fertility in peatlands can be done by analyzing the chemical properties of the soil. Analysis of the soil chemical properties includes analysis of the main element content such as acidity (pH), nitrogen (N), phosphorus (P), potassium (K) and cation exchange capacity (CEC). The physical properties of the soil consisting of the weight of the contents, the moisture content varies with different levels of burning, the higher the value of the weight of the contents, the more dense a soil and vice versa. In the value of water content, the amount of combustion influences the amount of ground water content, the more number of combustion, the value of water content also increases. Peat environmental conditions observed in the field consisted of soil moisture, soil temperature and ground water level measured for 7 days and obtained a mean value that also varied did not show its effect on the number of repeated fires. The chemical properties of peat soils on the number of repeated burning can increase and decrease each nutrient value consisting of N, P, K and also CEC. Nutrients that increase in the amount of combustion are pH, N, and CEC while the value of nutrients that decrease is K and P. This shows that the greater the level of combustion, the pH, N, and CEC greater.Keywords: peatlands, repeated burning, soil characteristics